THE ROLE OF TEACHER FEEDBACK IN IMPROVING STUDENTS' WRITING PERFORMANCE: A STRUCTURED NARRATIVE REVIEW FOR EFL CLASSROOMS - Cempa Huzaimah; Inayatul Muntaqiyah; Angela Mae Reyes (SENSEI RESEARCH CENTER, 2025)
Feedback from the teacher is very important in writing, but many students do not read the feedback and just look at the score. This article discusses the role of teacher feedback in improving students' writing performance. The method used is literature review from various international journals. The result shows that teacher feedback can improve the writing of the students, especially if the feedback is specific and the students are given a chance to revise. However, if the feedback is only correcting the grammar, the students do not learn much. So, the teacher must give feedback that is not only about the mistakes but also about how to improve the writing.